2014
DOI: 10.1080/09613218.2014.893161
|View full text |Cite
|
Sign up to set email alerts
|

A persona-based approach to domestic energy retrofit

Abstract: In order to improve the efficiency of the housing stock successfully, the offered technical solutions also need to meet occupants' needs and match their aspirations. Owner-occupiers present particular challenges: conflicting demands on their use of time and financial resources and their role as decision-makers for their own domestic renovation. A persona-driven study (based on user-centred design) was undertaken to explore the varying behaviours, attitudes and motivations towards home improvement for owner-occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 27 publications
2
70
0
Order By: Relevance
“…Scott et al (2014) found from a survey of 279 households residents believed that the physical changes being made to their homes would lead to significant savings on their energy bills and that residents experienced benefits relating to improved appearances of their neighbourhoods and increased sense of pride in their local communities. Haines and Mitchell (2014) identified from a study of 33 households living in solid wall properties in the East Midlands region that, despite the variation in motivation and engagement towards energy efficiency schemes, there is the potential for energy efficiency schemes to be used as a method to improve household value, improve internal comfort, improve social standing, and as a mechanism to climb the property ladder. These studies demonstrate the justifications for implementing energy efficiency measures in the home from a policy perspective but these reasons are not necessarily shared by those receiving these measures.…”
Section: Energy Efficiency In the English Housing Stockmentioning
confidence: 99%
“…Scott et al (2014) found from a survey of 279 households residents believed that the physical changes being made to their homes would lead to significant savings on their energy bills and that residents experienced benefits relating to improved appearances of their neighbourhoods and increased sense of pride in their local communities. Haines and Mitchell (2014) identified from a study of 33 households living in solid wall properties in the East Midlands region that, despite the variation in motivation and engagement towards energy efficiency schemes, there is the potential for energy efficiency schemes to be used as a method to improve household value, improve internal comfort, improve social standing, and as a mechanism to climb the property ladder. These studies demonstrate the justifications for implementing energy efficiency measures in the home from a policy perspective but these reasons are not necessarily shared by those receiving these measures.…”
Section: Energy Efficiency In the English Housing Stockmentioning
confidence: 99%
“…Recent sociotechnical research in the built environment and retrofit has begun to draw attention to this issue (e.g. Cole et al, 2008;Foulds et al, 2013;Gram-Hanssen, 2010;Haines & Mitchell, 2014;Ingle, Moezzi, Lutzenhiser, & Diamond, 2014;Judson & Maller, 2014;Karvonen, 2013;Tweed, 2013;Shove et al, 2008;Vlasova & Gram-Hanssen, 2014). This movement and the limitations of current POE have precipitated the authors' explicit adoption of the socio-technical approach for the FLASH project.…”
Section: Discussionmentioning
confidence: 99%
“…Whiteman and Irwig (1988) highlighted the need to plan a retrofit to ensure that all disruptive activities happen as early as possible in the process, therefore reducing users' dissatisfaction. According to Haines and Mitchell (2014), end users accept disruptions better if these are perceived to be less significant than the results of enhancement of comfort and space after the retrofit. Moreover, unexpected changes and execution delays can cause stress for tenants (Vadodaria et al, 2010).…”
Section: Bim In Retrofit Projectsmentioning
confidence: 99%
“…Table 1 presents a set of categories of disruption, which was identified in a literature review of retrofit projects. In summary, there is a need to develop detailed plans for the execution of retrofit works, as well as clear communication of the costs and technical solutions adopted, to enable users to perceive explicitly the benefits of the retrofit and make appropriate decisions (Miller and Buys, 2011;Sunikka-Blank et al, 2012;Wallace, 1986 Lee (2012), Haines and Mitchell (2014), Fawcett (2014) Tenants need to move out to avoid sharing the same space with workers Disruption of internal environment: happens when retrofit works affect the internal environment by generating different levels of pollution Noise provided by use of work tools such as hammers and mallets Whiteman and Irwig (1988), Ciria (2004), Miller and Buys (2011), Lee (2012), Jones (2013) Dust or debris resulting from demolition, building, plaster and so on Engineering Sustainability Building information modelling to cut disruption in housing retrofit Chaves, Tzortzopoulos, Formoso and Biotto enable users and workers to share effectively the same spaces during retrofit.…”
Section: Bim In Retrofit Projectsmentioning
confidence: 99%